1917 [videorecording (Blu-Ray + DVD)] - Mendes, Sam; Wilson-Cairns, Krysty; Newman, Thomas, 1955-; Deakins, Roger A., 1949-; Scott, Andrew, 1976 October 21-; Cumberbatch, Benedict, 1976-; Madden, Richard, 1986-; Strong, Mark, 1963-; Chapman, Dean-Charles, 1997-; Firth, Colin, 1960-; MacKay, George, 1992-; Mays, Daniel; et al. (Universal, 2020)
At the height of the First World War, two young British soldiers, Schofield and Blake are given a seemingly impossible mission. In a race against time, they must cross enemy territory and deliver a message that will stop a deadly attack on hundreds of soldiers, Blake's own brother among them.